2017
DOI: 10.1016/j.nlm.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

TDCS over the right inferior frontal gyrus disrupts control of interference in memory: A retrieval-induced forgetting study

Abstract: Retrieving information from episodic memory may result in later inaccessibility of related but task-irrelevant information. This phenomenon, known as retrieval-induced forgetting, is thought to represent a specific instance of broader cognitive control mechanisms, that would come into play during memory retrieval, whenever non-target competing memories interfere with recall of target items. Recent neuroimaging studies have shown an association between these mechanisms and the activity of the right Prefrontal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 72 publications
2
15
0
Order By: Relevance
“…The evidence also suggested that tDCS did not affect P3 latency measures or prEMG latencies. While our behavioral results contrast with some previous reports of SSRT reductions following anodal IFG stimulation [30][31][32][33][34][35][36] , they are in line with other studies failing to find any SSRT modulations 10,43 . This discrepancy could be driven by several methodological differences between this and earlier reports, such as experimental design, electrode locations, or stimulation lateralization.…”
Section: Discussionsupporting
confidence: 63%
“…The evidence also suggested that tDCS did not affect P3 latency measures or prEMG latencies. While our behavioral results contrast with some previous reports of SSRT reductions following anodal IFG stimulation [30][31][32][33][34][35][36] , they are in line with other studies failing to find any SSRT modulations 10,43 . This discrepancy could be driven by several methodological differences between this and earlier reports, such as experimental design, electrode locations, or stimulation lateralization.…”
Section: Discussionsupporting
confidence: 63%
“…While Cunillera et al (2014) reported a simultaneous modulation of two kinds of inhibition processes (reactive and proactive inhibition processes), by a-tDCS on the right IFG, using SST and GNGT, respectively. Additionally, Stramaccia et al (2017) revealed that tDCS over the right IFG disrupts control over interference using memory inhibition tasks. Therefore, one should take into consideration the type of task used to measure IC.…”
Section: Discussionmentioning
confidence: 99%
“…tDCS is a non-invasive tool that modulates brain function through hyper-or hypopolarization of neurons (Stagg and Nitsche 2011;Medeiros et al 2012). Stramaccia and coauthors reported evidence about the role of the right IFG in inhibition accuracy in SST (Stramaccia et al 2015) and, in interference control during memory retrieval processes (Stramaccia et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no effect of cathodal stimulation on SST performance was reported by studies using offline tDCS over the right inferior frontal gyrus (or, most recently, Stramaccia et al, 2015). Interestingly, in a study utilizing online tDCS, neither anodal nor cathodal stimulation affected SSRT (Stramaccia, Penolazzi, Altoè, & Galfano, 2017). Furthermore, some studies investigated the effects of cathodal stimulation on tasks similar to the SST, such as an anticipation timing task with a motor component (Hayduk-Costa, Drummond, & Carlsen, 2013), a cognitive reflection task (Oldrati, Patricelli, Colombo, & Antonietti, 2016), or a go/no-go task (Lapenta, Fregni, Oberman, & Boggio, 2012).…”
Section: Cathodal Tdcs and Its Effects On Response Inhibitionmentioning
confidence: 90%